The Islamic Enlightenment: The Modern Struggle Between Faith and Reason - Christoper de Bellaigue (The Bodley Head, 2017)
A highly original of the Clashes between islam and modernity in Istanbul, Cairo an Tehran in the last two hundred years. (Orhan Pamuk)